The total synthesis of D-chalcose and its C-3 epimer - Sun, Jun; Fan, Song; Wang, Zhan; Zhang, Guoning; Bao, Kai; Zhang, Weige (Beilstein Journal of Organic Chemistry, 2013)
We completed a new and efficient synthesis of D-chalcose (I) and the first synthesis of its C-3 epimer (I′) in nine steps with overall yields of 23% and 24%, respectively. The key steps in the sequence were the formation of the stereocenter on C3 via Grignard reaction, the introduction of the stereogenic center on C2 by Sharpless asymmetric dihydroxylation, the protection of the C1 and C2 hydroxy groups with tert-butyldimethylsilyl trifluoromethanesulfonate (TBSOTf), and the selective cleavage of the primary OTBS ether using catalytic DL-10-camphorsulfonic acid (CSA) in MeOH.
Keywords: asymmetric dihydroxylation; chalcose; epimer; total synthesis